Religious Development in the Digital Era: An Analysis of Public Interest in the Faculty of Da'wah and Communication Studies - Esli Zuraidah Siregar; Anas Habibi Ritonga; Nurharisyah Hasibuan; Masrul Efendi Umar Harahap; Nur Hasanah Hasibuan; Khairul Anwar (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2026)
This study aims to analyze religious development based on public interest in the Faculty of Da’wah and Communication Studies (FDIK) in the digital era. The research employs a quantitative approach using a survey technique targeting members of the public who have an interest in digitally based religious activities. The main variables include public perceptions, trust, interest, and intention toward FDIK as a center for the development of digital da’wah. The results indicate that public interest in FDIK falls within the high category, with mean scores exceeding 3.20 across all indicators. Perception and trust are shown to have a positive and significant influence on public interest, which subsequently encourages individuals’ intentions to participate in digital religious activities developed by FDIK. The findings further reveal that these two variables explain 64% of the variance in public interest, thereby demonstrating the relevance of Diffusion of Innovation Theory, Institutional Image, the Theory of Reasoned Action, and the Theory of Planned Behavior in understanding the dynamics of digital da’wah development. Overall, this study concludes that FDIK has strong prospects as a modern, adaptive, and community-oriented center for digital da’wah in the technological era. This research is expected to serve as positive scholarly literature in increasing student enrollment at the Faculty of Da’wah and Communication Studies, UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan.